Mediating Effect of Price Value on Effort Expectancy and Behavioral Intentions to Use Mobile Communication Technologies by Commercial Farmers in Uganda - Moya, Musa B.; Engotoit, Benard; Kituyi Mayoka, Geoffrey (Makerere University Business School, 2018)
This study examines the mediating role of Price Value on Effort Expectancy and Behavioural Intentions to Use mobile communication technologies by commercial farmers in Uganda. A cross sectional design and quantitative field survey method were adopted with 302 commercial farmers’ selected using snowball and purposive sampling techniques for the survey. Statistical mediation analysis was carried out using bootstrap mediation tool in Analysis of Moments Structures (AMOS) and Statistical Package for Social Sciences (SPSS) to test for mediation between the three variables of Price value, Effort Expectancy and Behavioural Intentions to Use. Price Value was found to mediate Effort Expectancy on Behavioural Intentions to use. From the findings, there is need for knowledge creation and market research so as to understand the unique needs of price value perceived by commercial farmers on mobile communication technologies, effort expectancy and behavioural intention on demand side. The study thus provides critical literature and evidence on the mediating role of Price value on relationship between Effort Expectancy and behavioural intention of mobile communication technologies by commercial farmers in resource constrained countries like Uganda. The study further proves that there exists a direct relationship between Price Value and Effort Expectancy; Effort Expectancy and Behavioural intentions to use of Mobile communication technologies. Policy makers need to design mobile phone policies and adopt strategies geared through Price Value, Effort Expectancy and Behavioral Intentions to use. It is also imperative that Policy frameworks support the establishment of robust, cost effective and easy to use Mobile communication technologies in ministry of agriculture to enhance service delivery.
Keywords: Mobile Communication Technologies (MCTs); Price Value (PV); Effort Expectancy (EE); UTAUT2; Behavioural Intentions to Use (BIU)